Expression of molecular markers of early and late lymphocyte activation and markers of autoimmune processes in patients with progressive myopia (Ukrainian Journal of Ophthalmology, 2026)
Introduction. In progressive myopia opposite changes are often observed in the immunological status, there is imbalance of the immunoregulatory mechanisms of the body, both in the direction of activation of the immune system, and in the direction of immunodeficient state that requires further investigation depending on the immunological status of the organism changes and progression of myopia. Objective: To study the T-cell-mediated and humoral immunity and peculiarities of the functional activity of the receptor apparatus of lymphocytes as well as study of the possibility of modifying lymphocyte receptor system by means of various drugs (berletion, glutoxim, tivortin) in adolescents with progressive myopia. Material and methods. 30 patients with progressive myopia were examined. All patients underwent determination of T-cell (CD 3, CD 4, CD 8) and humoral immunity (CD 19, IgA, IgM, IgG), natural killer cells CD 16, and the expression level of lymphocyte activation markers by immunohistochemistry. There were evaluated expression of activation markers CD7, CD 25, CD 38, CD 45, CD 54, CD 95, CD 150 and a marker of the autoimmune process CD 5. In vitro lymphocytes were cultured with drugs berletion, glutoxim, tivortin. Results. The patients with progressive myopia were marked to have increase in the number of T-helper cells, increased immunoregulatory index and content of Ig A as well as increased expression of the receptor molecules and markers of lymphocyte activation of the autoimmune process, which indicated the functional reserve mobilization of the immune system cells. Co-cultivation of drugs and peripheral blood lymphocytes of the patients with progressive myopia differentially alters the expression of the receptor molecules lymphocyte activation. Increased expression of CD7, CD 25, CD 45 against the background of the immutability of the expression CD 5 molecules when cultured with drugs berletion, glutoxim, tivortin indicates a balanced increase in the functional activity of lymphocytes.
Keywords: myopia; markers of lymphocyte activation